The Gene business who should control biotechnology? - Yoxen, Edward (London Pan Books, 1983)
Names corporations, scientists, and universities now manufacturing man-made organisms for medicine, agriculture and animal breeding, and chemistry, pointing out the potential for unconsidered & disastrous consequences beyond commercial success.
Chapter 1. The life industry -- Chapter 2. How life acquired a new meaning -- Chapter 3. The view from the cell -- Chapter 4. Selling a medical future -- Chapter 5. Speed-up at the plant -- Chapter 6. The pipeline into the future -- Chapter 7. We do we go from here?
Published in conjunction with Channel Four Television Company Limited.
Includes bibliographical references (pages 244-262) and index.
Keywords: Biotechnology; Genetic engineering; Biotechnology -- Social aspects; Genetic engineering -- Social aspects